2020
DOI: 10.1111/jace.17144
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure development and optical properties of Fe:ZnSe transparent ceramics sintered by spark plasma sintering

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Therefore, various types of thermal treatment of powders have been developed, taking into account the optimal relationship between impurity removal, particle growth, agglomeration, and phase transitions occurring in the process. Annealing is typically performed in the temperature range of 500-900 • C under vacuum [67,80,85], argon [79,83,84,[88][89][90], or hydrogen sulfide H 2 S/N 2 atmosphere [62][63][64]86]. Effective purification from oxygen-containing impurities begins at ~600 • C [62].…”
Section: Zinc Chalcogenide Optical Ceramic Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, various types of thermal treatment of powders have been developed, taking into account the optimal relationship between impurity removal, particle growth, agglomeration, and phase transitions occurring in the process. Annealing is typically performed in the temperature range of 500-900 • C under vacuum [67,80,85], argon [79,83,84,[88][89][90], or hydrogen sulfide H 2 S/N 2 atmosphere [62][63][64]86]. Effective purification from oxygen-containing impurities begins at ~600 • C [62].…”
Section: Zinc Chalcogenide Optical Ceramic Technologymentioning
confidence: 99%
“…The fabrication of ZnSe powders by chemical precipitation from solutions is usually carried out using NaHSe as a source of selenium ions [88,89]. Oxygen contamination is also an issue for the ZnSe; it is present in the powders in significant amounts and is detected both by XRD analysis and in the transmission spectrum of the synthesized ceramics [88].…”
Section: Zinc Chalcogenide Optical Ceramic Technologymentioning
confidence: 99%
“…Other ceramic systems such as Al 2 O 3 [23], MgO [24], MgAl 2 O 4 [16], ZrO 2 [14], or even Lu 3 NbO 7 [25] and Gd 3 TaO 7 [26] with cubic defect-fluorite structures, have also been reported. Non-oxide compositions have also been demonstrated, including nitrides (AlN [27] and AlON [28]), fluorides (MgF 2 [29], CaF 2 [30], SrF 2 [31], and BaF 2 [32]), and chalcogenides, such as sulfides (ZnS [33]), selenides (ZnSe [34]), and tellurates (KNbTeO 6 [35]). More recently, transparent ceramics have been successfully fabricated from high-entropy oxide [36] and fluoride [37] compositions, which were previously unattainable using conventional single-crystal growth processes.…”
Section: Transparent Ceramicsmentioning
confidence: 99%
“…However, the current literature provides little data on transparent non-oxide ceramics obtained through the glass crystallization route. The transparent non-oxide ceramics reported to date have been prepared only through the conventional powder processing approach, such as for ZnS [33,45], ZnSe [34], CaLa 2 S 4 [46], and others. One reason for this limitation is the lack of flexibility in the glass-forming process to enable fabrication of non-oxide transparent ceramics through glass crystallization.…”
Section: Transparent Ceramicsmentioning
confidence: 99%
“…Wang et al showed that the optical band gap of ZnS formed by one-pot hydrothermal procedure was decreased as it doped with Fe [3]. Yu et al found that Fe:ZnSe transparent ceramics prepared by co-precipitation method and spark plasma sintering have a reddish-brown color and can act as a promising mid-infrared laser material [12]. Mahmood et al found by applying the first-principle approach that the bandgap of ZnS can be tunable from ultraviolet to visible regions as it doped with iron doping [13].…”
Section: Introductionmentioning
confidence: 99%